Keabsahan Perjanjian Elektronik Sistem Cash on Delivery oleh Anak di Bawah Umur pada Social e-Commerce - Vidya Syalsyabilla Azzahra; Rhama Wisnu Wardhana (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This study analyzes the validity of cash on delivery (COD) transactions conducted by underage buyers through TikTok Shop By Tokopedia. This study uses a normative juridical method with statutory and conceptual approaches. The findings show that transactions conducted by minors are voidable agreements because they do not fulfill the legal capacity requirement under Article 1320 of the Indonesian Civil Code. As an electronic system operator, TikTok Shop is responsible for ensuring platform security and reliability in accordance with Government Regulation Number 71 of 2019. Therefore, stronger age verification systems and improvements to the COD payment method are needed through integration with official identities such as Population Identification Number or NIK.